The most-common phrasal verbs with their key meanings for spoken and academic written English: A corpus analysis. (May 2020) - Liu, Dilin; Myers, Daniel
English phrasal verbs (PVs) are ubiquitous and often polysemous. These lexical items are thus very important, but also challenging for ESL/EFL learners. Substantial research that can inform instructional approaches to PVs has already been conducted. One strand of this research has focused on identifying PVs that merit prioritization in learning. For example, Garnier and Schmitt (2015) developed a list of the most frequent meanings expressed by the 150 most common PVs. The present study extends their work by examining and comparing the meaning distributions of the 150 most common PVs in spoken English and in academic writing, arguably the two registers that ESL/EFL learners study the most. Using the spoken sub-corpus and the written academic sub-corpus of the Corpus of Contemporary American English, the study evaluates whether the proportional frequencies of PVs' meanings vary across the two registers. The results show a significant cross-register difference in an overwhelming majority of the 150 most common PVs. The findings suggest that instructional approaches to PVs should indeed prioritize different meanings of PVs depending on the kind of register learners engage with. A list of the PVs with their main meanings in each of the two registers is made available as anonline supplement .